Pengembangan Media Pembelajaran Berbasis Kartu Kuartet Arab dalam Meningkatkan Kosa Kata Siswa Kelas V - Deswara, Aditiya; Muhaemin; Syamsuddin, Naidin (Pedagogical Education and Review of Linguistics, 2025)
This study aims to identify the students' needs regarding Arabic language learning media, design and develop the media, and assess the effectiveness of the Arabic Quartet Card Game in enhancing Arabic vocabulary among fifth-grade students at Dunia Anak Islam School in Palopo. The study uses the 4D model, which includes the following stages: 1) Define, 2) Design, 3) Develop, and 4) Disseminate. The research was conducted at an elementary school with 9 fifth-grade students as subjects. Data was collected through questionnaires validated by experts in media, content, teachers, and student responses, and analyzed using both qualitative and quantitative methods. The developed product is a Quartet Card media for Arabic language teaching material at elementary schools. Validation results were as follows: media expert validation (91%), content expert validation (90%), teacher validation (95%), and student responses (94%), all categorized as "highly valid." The effectiveness test showed a significant improvement in students' vocabulary, with a post-test score of 95 and a pre-test score of 70 (t-hitung = 6.862 > t-table = 1.895), indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. The Arabic Quartet Card media was proven to be effective and suitable for use in teaching Arabic in elementary schools.